Modest Fashion: Diplomatic Creativity in Supporting Halal Tourism - Arin Fithriana; Woro Nopitasari (Universitas Muhammadiyah Mataram, 2018)
Halal has become a lifestyle that encompasses various aspects of life. The acceptance of halal standards is not only dominated by countries with Muslim populations, but also countries with a non-Muslim majority. This acceptance is based on an understanding of the sustainability and impact of halal products and services on whole life. Modest fashion Indonesia has spread worldwide and represents halal lifestyle. Modest fashion has become a tourist attraction and helped establish good relationship between Indonesia and world fashion. In this case, modest fashion serves as a tool of diplomacy. Unfortunately, modest fashion potency as supporter for tourism development has not been integrated well. This paper explores how modest fashion as a tool of diplomacy through creativity supports tourism. This is because the existence of tourism encourages multiplayer effects for other economic activities. Indonesia's cultural diversity and local wisdom should be an integral part of Indonesia's halal tourism. The contribution of fashion modest as a tool of diplomacy in creative industry to support halal tourism is analyzed using qualitative method through secondary data. The data show the development and acceptance of Indonesian modest fashion as well as its creativity utilizing culture and local wisdom has been widely accepted globally, but has not been fully exploited yet. Modest fashion has established good relationship between international actors. Integrating modest fashion with local wisdom and culture encourages the exploration of tourist destinations that are expected to encourage other halal standards in tourism. Ultimately it is expected to have a positive impact on sustainable development.